Determinants of Employee Performance PT. Perkebunan Nusantara in North Sumatra - Chandra, Dody Salden; Nainggolan, Edisah Putra; Hidayat, Rahmat (Journal of International Conference Proceedings, 2023)
This study aims to analyze the determinants of factors that influence the performance of employees of PT. Nusantara Plantations in North Sumatra. Employee Performance is influenced by several factors including Compensation, Authentic Leadership Style, and Intrinsic Motivation. The population in this study is PT. Perkebunan Nusantara in North Sumatra and taking samples in Medan City, namely PTPN II, and PTPN III. This study used a quantitative approach, the data were analyzed using multiple linear regression analysis techniques. The results of the study show that partially and simultaneously compensation, authentic leadership style, and intrinsic motivation have a positive and significant effect on employee performance.